A Troubled Marriage : Domestic Violence and the Legal System. - Goodmark, Leigh (NYU Press, 2011)
The development of a legal regime to combat domestic violence in the United States has been lauded as one of the feminist movement's greatest triumphs. But, Leigh Goodmark argues, the resulting system is deeply flawed in ways that prevent it from assisting many women subjected to abuse. The current legal response to domestic violence is excessively focused on physical violence; this narrow definition of abuse fails to provide protection from behaviours that are profoundly damaging, including psychological, economic, and reproductive abuse. The legal system is deaf to the claims of women who de.